2009
DOI: 10.1096/fasebj.23.1_supplement.653.1
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Np95 and Eme1 in the DNA damage response

Abstract: Methyl methansulfonate UV sensitive clone 81 (Mus81) and essential meiotic endonuclease 1 (Eme1) form a heterodimeric endonuclease that preserves genomic integrity through the repair of DNA replication‐associated damage. Despite its role as genome guardian and tumour suppressor, our understanding of how this endonuclease is coordinated during the DNA damage response is poor. In order to identify other proteins that interact with Mus81‐Eme1, our laboratory conducted a protein interaction screen to identify and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…While our study revealed the molecular details of PI5P-mediated allosteric control of hUHRF1, defining the physiological role of such regulation events remains a major challenge. hUHRF1 interacts with several factors associated with the DNA damage response such as Eme1, TIP60, Ku70, and PARP1 (62)(63)(64). Because H3K9me3 has an important role in repair mechanisms of DNA damage (65), we speculate that hUHRF1 might recruit repair factors to H3K9me3enriched heterochromatic loci, which are otherwise inaccessible (34).…”
Section: Discussionmentioning
confidence: 99%
“…While our study revealed the molecular details of PI5P-mediated allosteric control of hUHRF1, defining the physiological role of such regulation events remains a major challenge. hUHRF1 interacts with several factors associated with the DNA damage response such as Eme1, TIP60, Ku70, and PARP1 (62)(63)(64). Because H3K9me3 has an important role in repair mechanisms of DNA damage (65), we speculate that hUHRF1 might recruit repair factors to H3K9me3enriched heterochromatic loci, which are otherwise inaccessible (34).…”
Section: Discussionmentioning
confidence: 99%